Local authorities planning for urban sustainability - towards implementing energy conservation policies in development plan - Ho, Chin Siong (Faculty of Built Environment, UTM, 2008)
This study aims to examine lessons learned from local authorities in United Kingdom on how policies on energy conservation can be incorporated in their development plan. Two' cases of different levels of urban development and population size are chosen as case studies to understand the feasibilities of implementation of energy conservation policies in development plan. Since urban planning in Malaysia is based on British model of development plan and development control system, this study may provide directions and guidance in the implementation of energy conservation in a local planning authority area.